1998
DOI: 10.1093/humrep/13.11.3197
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial protein PP14 and CA-125 in recurrent miscarriage patients; correlation with pregnancy outcome

Abstract: The concentrations of endometrial proteins PP14 and CA-125 were measured in uterine flushings taken on days LH+10 and LH+12 (10 and 12 days after luteinizing hormone surge) of the menstrual cycle from 15 normal, fertile women and 49 women who suffered recurrent miscarriage. The concentration of PP14 was significantly lower in the flushings from the recurrent miscarriage patients than in those from fertile controls on both day LH+10 (median: 1300, range: 3-10 300 ng/ml versus median: 13 933, range: 2174-40 404 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 18 publications
4
44
0
2
Order By: Relevance
“…In such conditions, subnormal glycodelin concentrations have been reported in endometrium, uterine flushings and serum at the time of expected endometrial receptivity (82)(83)(84)(85). Both glycodelin mRNA and protein are downregulated in human first trimester miscarriage (86), and pregnant women with polycystic ovary syndrome (PCOS), who subsequently miscarry show subnormal rise of glycodelin serum concentration during the first trimester, compatible with weaker placentation (87).…”
Section: Conditions Related To Implantation and Placentation Failurementioning
confidence: 99%
“…In such conditions, subnormal glycodelin concentrations have been reported in endometrium, uterine flushings and serum at the time of expected endometrial receptivity (82)(83)(84)(85). Both glycodelin mRNA and protein are downregulated in human first trimester miscarriage (86), and pregnant women with polycystic ovary syndrome (PCOS), who subsequently miscarry show subnormal rise of glycodelin serum concentration during the first trimester, compatible with weaker placentation (87).…”
Section: Conditions Related To Implantation and Placentation Failurementioning
confidence: 99%
“…Progesterone (15,16), relaxin (17,18), and chorionic gonadotropin (19) have been proposed as the major physiological stimuli of glycodelin synthesis and secretion by the primate endometrium. Low glycodelin concentrations were observed in secretory phase uterine flushings from women with a history of recurrent miscarriages (20). Although functional studies are limited, preliminary data indicate that glycodelin has immunosuppressive effects that are postulated to facilitate the embryonic evasion of the maternal immune response (21).…”
mentioning
confidence: 99%
“…One report demonstrated that concentration of CA-125 in the pregnant women who subsequently aborted were higher than those who did not, thus suggesting that serum CA-125 are not so important in maintaining successful pregnancy (27). CA-125 may be useful in the assessment of endometrial development in recurrent miscarriage patients and this suggested the importance in preparing the endometrium for embryo implantation (28). High level of serum CA-125 with high lactate dehydrogenase indicates more extensive trophoblastic tissue damage (29).…”
Section: Discussionmentioning
confidence: 99%